2020
DOI: 10.12659/msm.919460
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Splicing Factor 3b Subunit 1 (SF3B1) Reduced Cell Proliferation, Induced Apoptosis and Resulted in Cell Cycle Arrest by Regulating Homeobox A10 (HOXA10) Splicing in AGS and MKN28 Human Gastric Cancer Cells

Abstract: Background: Small nuclear ribonucleoproteins (snRNPs) complexes of protein and noncoding RNA accumulate in the cell nucleus and catalyze pre-mRNA splicing to form the spliceosome. This study aimed to investigate the role of the spliceosome, splicing factor 3b subunit 1 (SF3B1), in AGS and MKN28 human gastric cancer cells in vitro, including gene knockdown with small interfering RNA (siRNA), and the use of the selective mRNA splicing inhibitor of SF3B1, pladienolide B. Material/Methods: In AGS and MKN28 human g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…SF3B1 is an important regulator of pre-mRNA machinery 24,40,41 and we found that KSR2 transcript levels were abrogated with SF3B1 knockdown (Fig. 8a).…”
Section: Ksr2 Contributes To Sf3b1-dependent Proliferation In Endometmentioning
confidence: 76%
See 1 more Smart Citation
“…SF3B1 is an important regulator of pre-mRNA machinery 24,40,41 and we found that KSR2 transcript levels were abrogated with SF3B1 knockdown (Fig. 8a).…”
Section: Ksr2 Contributes To Sf3b1-dependent Proliferation In Endometmentioning
confidence: 76%
“…Here, we also found SF3B1 transcriptome enriched with several metabolic process, suggesting a possible role for SF3B1 in metabolic programming in cancers. It is well-recognized that SF3B1 regulate alternative splicing of several crucial genes involved in cell survival pathways implying its oncogenic potential in promoting tumorigenesis 24 , 40 , 41 . Consistently, we found wide scale disruption of alternative splicing across the transcriptome, suggesting that SF3B1- driven alternative splicing has a pathogenic significance in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During routine culturing of the iPSC lines, the patient lines required less frequent passaging than iPSC lines derived from healthy individuals. Given the importance of TXNL4A in the spliceosome and of pre-mRNA splicing in all aspects of cell function and behaviour, it was very likely that reduced expression of this core pre-mRNA splicing factor would compromise in some way the ability of cells to grow and/or proliferate, as with other models of human splicing factor knockdown or inhibition [58,62]. We therefore performed a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) tetrazolium assay to quantify any differences in proliferative rate between the iPSC lines.…”
Section: Bmks Patient Ipscs Proliferate Slowly But Are Not More Apoptmentioning
confidence: 99%
“…[13] In AGS and MKN28 human gastric cancer cells, the expression of the Homeobox A10 (HOXA10) gene, a potential effector oncogene of alternative splicing, was up-regulated due to SF3B1 mutations, subsequently leading to the manipulation of the downstream target genes of the HOXA10. [28] Very recently, Abdel-Wahab and Bradley group found that diverse SF3B1 mutations converged on suppression of BRD9, which is a core component of the noncanonical BAF complex. BRD9 showed notable mis-splicing in all patients with SF3B1-mutant cancers, including CLL, MDS and UM.…”
Section: Introductionmentioning
confidence: 99%
“…Point mutations in the HEAT repeats domain of SF3B1 observed recurrently in patients result in the selection of alternative BP sites and thereby induce the usage of cryptic 3’SSs and subsequently the generation of abnormally spliced mRNA [25,26] . Many mis‐spliced genes have been identified [13,15,27,28,29] in SF3B1‐mutant samples. For example, in a gene‐expression profiles analysis of cell samples obtained from patients with MDS, 94 gene sets (of 1673 screened) were identified and found to be down‐regulated in patients with SF3B1 mutations; further study showed that SF3B1 mutations were related to systematic down‐regulation of essential mitochondrial gene networks [13] .…”
Section: Introductionmentioning
confidence: 99%